2009
DOI: 10.1016/j.clim.2008.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Severe combined immunodeficiency (SCID) and attention deficit hyperactivity disorder (ADHD) associated with a coronin-1A mutation and a chromosome 16p11.2 deletion

Abstract: Defects causing severe combined immunodeficiency (SCID) have been reported in pathways mediating antigen receptor rearrangement, antigen receptor and cytokine signaling, and purine metabolism. Recognizing that the actin regulator Coronin-1A is essential for development of a normal peripheral T cell compartment in mouse models, we identified absence of Coronin-1A in a girl with T-B+NK+ SCID who suffered recurrent infections including severe post-vaccination varicella at age 13 months. Murine Coronin-1A is essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(115 citation statements)
references
References 30 publications
3
110
0
2
Order By: Relevance
“…Genetic details of the Coro1A-deficient patient will be described elsewhere, but c.1077delC (maternal source) and c.248_249delCT (paternal source) mutations were identified in the patient initially via wholeexome sequencing and were subsequently confirmed using the Sanger method. The c.248_249delCT mutation has been previously reported (29).…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…Genetic details of the Coro1A-deficient patient will be described elsewhere, but c.1077delC (maternal source) and c.248_249delCT (paternal source) mutations were identified in the patient initially via wholeexome sequencing and were subsequently confirmed using the Sanger method. The c.248_249delCT mutation has been previously reported (29).…”
Section: Methodsmentioning
confidence: 89%
“…All previously described Coro1A-deficient patients have seemingly unaffected NK cell numbers; however, NK cells have not been studied functionally before now (26,29,30). It is relevant that these patients have recurrent and severe viral infections, and one of these patients was hospitalized with near-fatal varicella infection (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, it has been demonstrated that 16p11.2 is strongly associated with a group of neural developmental disorders, including autism spectrum disorder 9 [14,15], schizophrenia [18], attention-deficit hyperactivity disorder [29] and abnormal head size [30]. Deletion or duplication of one copy of the 16p11.2 interval is tightly associated with impaired brain function, indicating the importance of 16p11.2 gene domain [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The former clinical scenario has been described in a patient with severe combined immunodeficiency due to Coronin-1A (MIM 605000) mutation and a 16p11.2 deletion. 12 The rearranged 16p11.2 interval contains 27 annotated genes, some of which are potential candidates for the various phenotypes in patients with these copy number changes. The TBX6 (MIM 602427) gene encodes a transcription factor important in developmental processes and can have a role in the congenital spinal anomalies that we observed in our patients.…”
Section: Discussionmentioning
confidence: 99%